Babylonian Witchcraft Literature: Case Studies - Abusch, I. Tzvi (Book collections on Project MUSE., 2020)
"The studies in this volume focus on individual Babylonian magical texts while developing an overall understanding of these texts as a whole. Part One follows a diachronic approach, Part Two a synchronic one. In this sense, the studies are to be viewed broadly: while unravelling knots in individual texts, they highlight certain issues and exemplify some solutions for common problems in traditional Mesopotamian therapeutic literature."--Provided by publisher